Monitoring of Post-fire Vegetation Succession on Peatland in Bengkalis Island, Riau Province - Pudjawati, Nihawa Hajar; Pulunggono, Heru Bagus; Asy'Ari, Rahmat; Zulfajrin, Moh; Nurazizah, Lina Lathifah; Saputri, Hanum Resti; Rivai, Fathan Aldi; Setiawan, Yudi (Media Konservasi, 2025)
Peatlands are characterized by the accumulation of decomposed plant remains, which result in an organic carbon content of approximately 16 percent and form a layer at least 40 cm thick. Peat ecosystems play a crucial role in supporting biodiversity conservation, maintaining water availability, and regulating the climate. However, human activities threaten these functions, especially during the dry season, which often leads to extensive fires. Post-fire succession is a natural process through which the land attempts to restore its original state. Monitoring succession after peatland fires can be conducted using satellite-based remote sensing technology, which provides spatiotemporal information. This study utilized a time series of three Landsat satellites, namely Landsat 5 (TM), Landsat 8 (OLI), and Landsat 9 (OLI2), to monitor succession in burnt peat areas on Bengkalis Island from 2000 onward. Additionally, hotspot data from FIRMS NASA  and MODIS were incorporated. The results showed a total of 3,689 hotspots recorded between 2005 and 2023. The confirmed land cover types in the succession area include swamps, water bodies, and oil palm plantations. The information from this research is expected to inform policymaking by the government or peatland area managers, and serve as a reference for further studies.